Gossamer - Lowry, Lois. (New York, NY : Houghton Mifflin Company, 2006)
While learning to bestow dreams, a young dream giver tries to save an eight-year-old boy from the effects of both his abusive past and the nightmares inflicted on him by the frightening Sinisteeds.
"Walter Lorraine books."
G4
Keywords: Dreams -- Fiction; Nightmares -- Fiction; Foster home care -- Fiction; Child abuse -- Fiction